MAIN DIFFERENCES BETWEEN HYMENOLEPIS NANA AND HYMENOLEPIS DIMINUTA (CIPEEX, 2025)
This summary describes the main differences between Hymenolepis nana and Hymenolepis diminuta, both flatworms of the Hymenolepididae family. These tapeworms parasitize humans and animals, causing hymenolepiasis. The differences include life cycle, host type, transmission mode, and morphology of eggs and larvae.Hymenolepis nana can parasitize the human small intestine, with a shorter, simpler life cycle that includes autoinfection. It can have a monoxenic or heteroxenic biological cycle. Transmission occurs via the fecal-oral route and is more common in areas with poor sanitation. The tapeworm measures 2–4 cm and is known as the dwarf tapeworm. Its eggs are nearly spherical, transparent, with thin outer and inner membranes.Hymenolepis diminuta, the rat tapeworm, primarily parasitizes rodents, rarely affecting humans. It has a heteroxenic cycle requiring an insect as an intermediate host. Transmission occurs through food contaminated with infected insects. Adult worms measure 20–60 cm. Its eggs are spherical, yellowish-brown, with a thicker outer membrane compared to H. nana.Both parasitoses are generally asymptomatic or involve mild gastrointestinal disorders. Understanding these differences is crucial for proper diagnosis, treatment, and breaking the epidemiological chain.
Keywords: platelmintos; cestoda; hymenolepis nana; hymenolepis diminuta